2021
DOI: 10.1186/s12944-021-01491-z
|View full text |Cite
|
Sign up to set email alerts
|

A review on gut microbiota: a central factor in the pathophysiology of obesity

Abstract: Obesity and its complications constitute a substantial burden. Considerable published research describes the novel relationships between obesity and gut microbiota communities. It is becoming evident that microbiota behave in a pivotal role in their ability to influence homeostatic mechanisms either to the benefit or detriment of host health, the extent of which is not fully understood. A greater understanding of the contribution of gut microbiota towards host pathophysiology is revealing new therapeutic avenu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 127 publications
(175 reference statements)
1
41
0
2
Order By: Relevance
“…In line with the well-established literature 48 , the fecal microbiome was profoundly affected by high-fat feeding, with a markedly reduced diversity as compared to control mice. Our previous work demonstrated that the species Akkermansia muciniphila of the Verrucomicrobia phylum was increased at ZT14 compared to ZT2, and was both increased and arrhythmic following WD-feeding, in parallel with the time- and diet-dependent changes in GLP-1 secretory responses 21 .…”
Section: Discussionsupporting
confidence: 84%
“…In line with the well-established literature 48 , the fecal microbiome was profoundly affected by high-fat feeding, with a markedly reduced diversity as compared to control mice. Our previous work demonstrated that the species Akkermansia muciniphila of the Verrucomicrobia phylum was increased at ZT14 compared to ZT2, and was both increased and arrhythmic following WD-feeding, in parallel with the time- and diet-dependent changes in GLP-1 secretory responses 21 .…”
Section: Discussionsupporting
confidence: 84%
“…Different factors have been associated with obesity: a high calorie diet, an increase in sedentary activity, and genetic factors. These causal factors could also be related to changes in the gut microbiota, resulting in disruption to the bacterial community, known as dysbiosis, affecting the host–microorganism relationship, energy homeostasis, metabolic function, and inducing inflammation [ 4 , 5 ]. There are several mechanisms involving gut microorganisms and the host, such as the regulation of fermentation and polysaccharide absorption from diet, protection of gastrointestinal mucosa permeability, etc.…”
Section: Introductionmentioning
confidence: 99%
“…An increasing number of studies have explored a possible bidirectional connection between gut microbiota and the brain, for which the term gutbrain axis has been coined [3,4]. Moreover, the link between the gut microbiota and human diseases is more and more evident as alterations in gut microbial community composition have been reported in several pathological conditions including neurological and autoimmune disorders, obesity and cancer [5][6][7][8][9][10]. The microbiome studies on a transgenic AD model and patients highlighted alterations in gut microbiota providing new understanding of AD and additional features for its pathological characterization [11,12].…”
Section: Introductionmentioning
confidence: 99%